Inorganic Constituents in Coal - Rađenović A. (Kemija u Industriji, 2006)
Coal contains not only organic matter but also small amounts of inorganic constituents. More thanone hundred different minerals and virtually every element in the periodic table have been foundin coal. Commonly found group minerals in coal are: major (quartz, pyrite, clays and carbonates),minor, and trace minerals. Coal includes a lot of elements of low mass fraction of the orderof w=0.01 or 0.001 %. They are trace elements connected with organic matter or minerals comprisedin coal. The fractions of trace elements usually decrease when the rank of coal increases.Fractions of the inorganic elements are different, depending on the coal bed and basin. A varietyof analytical methods and techniques can be used to determine the mass fractions, mode ofoccurrence, and distribution of organic constituents in coal. There are many different instrumentalmethods for analysis of coal and coal products but atomic absorption spectroscopy – AAS is theone most commonly used. Fraction and mode of occurrence are one of the main factors that haveinfluence on transformation and separation of inorganic constituents during coal conversion.Coal, as an important world energy source and component for non-fuels usage, will be continuouslyand widely used in the future due to its relatively abundant reserves. However, there is aconflict between the requirements for increased use of coal on the one hand and less pollution onthe other. It’s known that the environmental impacts, due to either coal mining or coal usage, canbe: air, water and land pollution. Although, minor components, inorganic constituents can exert asignificant influence on the economic value, utilization, and environmental impact of the coal.